Glutamate and capsaicin effects on trigeminal nociception I: Activation and peripheral sensitization of deep craniofacial nociceptive afferents - Lam, David K. (2008)
We have examined the effect of the peripheral application of glutamate and capsaicin to deep craniofacial tissues in influencing the activation and peripheral sensitization of deep craniofacial nociceptive afferents. The activity of single trigeminal nociceptive afferents with receptive fields in deep craniofacial tissues were recorded extracellularly in 55 halothane-anesthetized rats. The mechanical activation threshold (MAT) of each afferent was assessed before and after injection of 0.5M glutamate (or vehicle) and 1% capsaicin (or vehicle) into the receptive field. A total of 68 afferents that could be activated by blunt noxious mechanical stimulation of the deep craniofacial tissues (23 masseter, 5 temporalis, 40 temporomandibular joint) were studied. When injected alone, glutamate and capsaicin activated and induced peripheral sensitization reflected as MAT reduction in many afferents. Following glutamate injection, capsaicin-evoked activity was greater than that evoked by capsaicin alone, whereas following capsaicin injection, glutamate-evoked responses were similar to glutamate alone. These findings indicate that peripheral application of glutamate or capsaicin may activate or induce peripheral sensitization in a subpopulation of trigeminal nociceptive afferents innervating deep craniofacial tissues, as reflected in changes in MAT and other afferent response properties. The data further suggest that peripheral glutamate and capsaicin receptor mechanisms may interact to modulate the activation and peripheral sensitization in some deep craniofacial nociceptive afferents.